Unproductive Co-production: European Integration, the British Film Industry and the Franco-British Co-production Agreement of 1965. Issue 2 (April 2021) - Stubbs, Jonathan
Abstract : The negotiation of bilateral co-production agreements had a major impact on European film-making from the 1950s to the 1970s. These agreements also provided the basis for the closer integration of Europe's film industries within what was then the European Economic Community (EEC). However, the British government was slow to adopt co-production arrangements and British film-makers tended to be more reticent about using them once they were made available. This article examines the British experience of European co-production during this period, focusing on the negotiation and implementation of the Franco-British co-production agreement of 1965 in the context of broader debates about film production and policy within the EEC. Particular attention is given to Someone Behind the Door (1971), a proposed Franco-British film which was ultimately made as a collaboration between French and Italian production companies after delays on the British side caused the French producer to withdraw from the UK. The correspondence collected by the Department of Trade and Industry (DTI) as the proposal for Someone Behind the Door was processed – including input from film union and producer associations – provides a unique insight into the bureaucratic policies and procedures which encumbered European co-production in Britain. While continental film-makers established comfortable habits of cooperation, British co-production was stymied from the outset by a misalignment between the interests of Britain's government, its film unions and its producers.